Efficacy and safety of afatinib for non-small-cell lung cancer: state-of-the-art and future perspectives. Issue 7 (2nd July 2020) - Sartori, Giulia; Belluomini, Lorenzo; Lombardo, Fiorella; Avancini, Alice; Trestini, Ilaria; Vita, Emanuele; Tregnago, Daniela; Menis, Jessica; Bria, Emilio; Milella, Michele; Pilotto, Sara
ABSTRACT: Introduction: Afatinib is a second-generation epidermal growth factor receptor ( EGFR ) tyrosine kinase inhibitor, acting as an irreversible and multitarget blocker of ErbB family members. Afatinib is currently approved for advanced non-small-cell lung cancer (NSCLC) harboring common and uncommon sensitizing EGFR mutations and for squamous NSCLC patients progressing after first-line platinum-based chemotherapy. Areas covered: This review summarizes the efficacy and safety profile of afatinib compared with chemotherapy and other EGFR TKIs, in order to evaluate its characteristics and potential role in the increasingly complex treatment landscape of EGFR -mutant lung cancer. Future perspectives and innovative drug combinations are also discussed. Expert opinion: Afatinib has been demonstrated to improve efficacy and quality of life compared with chemotherapy with a managed toxicity profile. However, in recent years, the increasing availability of different treatment options for advanced EGFR -mutant NSCLC has made the current treatment scenario more complicated, with an increasing need of new and deeper scientific data. In this light, the identification and validation of potential clinicopathological and/or molecular predictors of benefit, as well as the clarification of resistance mechanisms, may help to clarify the most appropriate treatment strategies and sequences for EGFR -mutant patients.